Uji Efektivitas Ekstrak Daun Cengkeh (Syzygium aromaticum L.) untuk Menghambat Pertumbuhan Colletotrichum sp. Penyebab Penyakit Antraknosa pada Buah Pepaya (Carica papaya L.) - FITRIANA, FIRA; SUDARMA, I MADE; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2023)
Effectiveness of Clove Leaf Extract ( Syzygium aromaticum  L.) to Inhibit the Growth of  Colletotrichum  sp. Causes Anthracnose Disease on Papaya Fruit ( Carica papaya  L.) Papaya ( Carica papaya  L.) is a fruit that has high economic value. Papaya production in Indonesia fluctuates, one of which is due to anthracnose disease caused by  Colletotrichum  sp. Environmentally friendly controls that can be used are botanical fungicides. Clove leaf is a plant material that is antifungal. This study aims to determine the effectiveness of clove leaf extract to inhibit the growth of  Colletotrichum  sp. causes anthracnose on papaya fruit. This study used a completely randomized design. Inhibition test of clove leaf extract by colony method and MIC ( Minimum Inhibitory Concentration )  in vitro  using extract concentration 0%; 0,1%; 0,2%; 0,3%; 0,4%; 0,5%; 0,6%; 0,7%; 0,8%; 0,9%; 1%; 2%; 3%; 4%; 5%.  In vivo  test of the effectiveness of clove leaf extract against  Colletotrichum  sp. on papaya fruit using extract concentration 0%; 1%; 2%; 3%; 4%; 5%. The results showed that clove leaf extract concentrations of 3%, 4%, 5% effectively inhibited the growth of  Colletotrichum  sp. with 100% inhibition and MIC value was 0,1%.  In vivo  results showed clove leaf extract with concentrations of 4% and 5% effectively inhibited  Colletotrichum  sp. colonies and suppressed infection on papaya fruit with the percentage of colony inhibition and fruit damage inhibition respectively 71,22%; 76,48% and 71,44%; 76,93%.